Evaluation of Regional Policy Capacity in Improving Access and Quality of Education: Comparative Analysis of Region in Southwest Papua Province - Iskandar, Didik (ASHA Publishing, 2025)
This study examines regional policy capacity variations and their impact on educational access and quality across five districts in Papua Barat Daya Province, Indonesia. Using a cross-sectional comparative design, data were collected from 150 key informants through structured surveys and secondary sources from 2020 to 2024. Policy capacity was measured using a composite index comprising five dimensions: institutional, human resource, financial, technological, and coordination capacities. Educational outcomes were assessed through school participation rates, teacher-student ratios, infrastructure availability, national examination scores, literacy rates, and dropout rates. Principal component analysis validated the composite index construction, while multiple regression analysis examined predictive relationships between capacity dimensions and educational outcomes. Results reveal significant inter-district variations in policy capacity, ranging from 78.2 in Sorong Regency to 58.6 in Tambrauw Regency. Strong correlations (r = 0.791-0.879, p < 0.01) were found between policy capacity and educational indicators, with institutional capacity emerging as the strongest predictor across all regression models (R² = 0.742-0.785). The findings demonstrate that administrative capacity serves as a fundamental determinant of educational performance in decentralized systems. The study recommends differentiated capacity-building strategies, with intensive support for underperforming regions and leveraging successful models from high-performing districts. These results contribute to understanding decentralized governance effectiveness and provide evidence-based recommendations for improving educational equity in Indonesia's remote provinces.